The Clinical Studies about improvement rate in managering patients who had lumbago and pain in loin & feet with herbal-acupunture therapy - Wei Tung-Shuen; Lee Dong-Hyun; Kim Hyo-Soo (Korean Pharmacopuncture Institute, 2004)
Objectives : The purpose of this study is to compare the improvement rate in managering patients who had lumbago and pain in loin & feet by herbal-acupunture therapy with conservative treatment. Methods : 40patients who invited from March. 2003 to May. 2004 with lumbago and pain in loin & feet inve, were divided into two classes. A class was managed with conservative treatment(acupuncture, herb med, negative therapy, bed rest and physical therapy) and herbal-acupuncture therapy, the other class was managed with conservative treatment only. Two classes were distributed by sex and age, therapeutic periods, radiolographic results and therapeutic results that checked with VAS(visual analog scale) and ODI(Oswestry disability index). Results : According to VAS and ODI results, A class was managed with conservative treatment and herbal-acupuncture therapy shows the improvement in controling the pain of lumbago etc. comparing with the other class.